Characterizing inquiry-based science classroom learning environments—generative or replicative—using teachers’ epistemic orientations: a qualitative study - Akuoko, Eric Antwi; Fulmer, Gavin W.; Hand, Brian; Suh, Jee; Gardner, Grant (Frontiers in Education, 2025)
This study examines the relationship and influences between teacher epistemic beliefs and their learning environment. Drawing on a multiple case study design, six in-service elementary school science teachers were purposefully selected from a larger, NSF-funded study of teachers’ adaptive expertise in the epistemic complexities of science teaching. Methods involved hypothesis, open, and integrative cross-case & cross-strata analyses of epistemic orientation surveys, field observation notes, semi-structured interviews, vignettes, and Teacher Implementation scores, demonstrate that teacher beliefs/orientation type are associated with classroom environment type characterization. Further, results show that struggles of teachers mirrored elementary school science teachers’ sense of control, persistence, and adaptive expertise. Major findings from the study reveal that participants who exhibited rigid epistemic beliefs and fluid/flexible epistemic beliefs tended to establish replicative and generative learning environments respectively, albeit on a continuum. And that, while teachers with flexible epistemic belief showed increased teacher adaptive expertise and co-shared classroom authority/control, teachers with rigid epistemic belief struggled to release control and were generally less adaptive/persistent. Finally, the study discusses pertinent implications for policy, practice, and research. For policy, framers of standards documents, policy makers of teacher preparation, and curriculum developers should consider teacher beliefs and attitudes as foundational for framing future science standards. Regarding practice, the study suggests a reconstruction of belief systems about knowledge and knowing or a total shift in epistemic beliefs for practice. Future research could explore the synergy of all the data sets by adopting a multi-perspective approach for their study.